2020
DOI: 10.3390/nu12092808
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Human Milk Oligosaccharides on the Adult Gut Microbiota and Barrier Function

Abstract: Human milk oligosaccharides (HMOs) shape the gut microbiota in infants by selectively stimulating the growth of bifidobacteria. Here, we investigated the impact of HMOs on adult gut microbiota and gut barrier function using the Simulator of the Human Intestinal Microbial Ecosystem (SHIME®), Caco2 cell lines, and human intestinal gut organoid-on-chips. We showed that fermentation of 2’-O-fucosyllactose (2’FL), lacto-N-neotetraose (LNnT), and combinations thereof (MIX) led to an increase of bifidobacteria, accom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
104
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(105 citation statements)
references
References 68 publications
1
104
0
Order By: Relevance
“…Using the Simulator of the Human Intestinal Microbial Ecosystem (SHIME ® ), Šuligoj et al [ 59 ] recently reported that fermentation of 2′-FL resulted in a simultaneous increase in Bifidobacterium and SCFAs including butyrate in particular. In our in vitro experiments, fermentation of stool samples with 2′-FL also resulted in a simultaneous increase in Bifidobacterium and SCFAs including butyrate.…”
Section: Discussionmentioning
confidence: 99%
“…Using the Simulator of the Human Intestinal Microbial Ecosystem (SHIME ® ), Šuligoj et al [ 59 ] recently reported that fermentation of 2′-FL resulted in a simultaneous increase in Bifidobacterium and SCFAs including butyrate in particular. In our in vitro experiments, fermentation of stool samples with 2′-FL also resulted in a simultaneous increase in Bifidobacterium and SCFAs including butyrate.…”
Section: Discussionmentioning
confidence: 99%
“…HMOs, through metabolism into short chain fatty acids and cross feeding with butyrate-producing bacteria, induce butyrate production in the colon. Butyrate is an essential metabolite, as it forms the preferable energy source for colon epithelial cells, contributes to the preservation of the gut barrier, and displays immunomodulatory effects [ 224 ]. Therefore, HMOs support barrier function through promotion of the formation of fermentation products, especially by Bifidobacterium [ 225 ].…”
Section: A Review Of Human Milk Oligosaccharides (Hmos)mentioning
confidence: 99%
“…Such condition includes ageing, irritable bowel syndrome, or inflammatory bowel disease. However, the exact mechanism of these effects remains to be largely explored [ 224 ].…”
Section: A Review Of Human Milk Oligosaccharides (Hmos)mentioning
confidence: 99%
See 2 more Smart Citations